Avaliação do padrão de desempenho das equipes técnicas de mamografia frente ao uso de tecnologias digitais - Oliveira, Evelyn Rosa de (2017)
This study presents a rejection analysis performed at the clinic Diagnóstico Avançado Por Imagem - DAPI, with data from 647 rejected mammograms performed three months before and three months after a training session of the mammography team, to analyze the performance of them after the training. The information was collected in the database of mammography rejection analysis software,these data include: Incidence; Number of repetitions; Reason for the repetition; Identification of the professional; Rejection examination and accepted examination. It was observed that, after the training, the rejection indexes by positioning (the greatest cause of the rejections) were reduced. It was observed that the group developed rigorous criteria, which also contributed to increase the repetitions after the training. The most rejected incidence was Cranio Caudal Right - CCD, both before (32%) and after training (36%).The analysis of the performance of the technical team, in relation to the quality criteria in digital mammography, could be performed by the individual analysis of the professionals to contribute to the qualification of the team and to increase the quality of the exams. The "A" professional, who had the highest index of rejection by positioning, after the training there was a reduction of 17% of the repetitions due to improper positioning. Acceptable quality images have been identified that are rejected unnecessarily 8% before and 3,6% after training. Before the training, the technical team performed the mammograms with values of compression between 80 and 89 N, and after training most of the exams were performed with 90 N or more. This increase which results in better quality tests and lower dose for the patient.